1995
DOI: 10.1002/mrm.1910340409
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in the motor cortex of resting human brain using echo‐planar mri

Abstract: An MRI time course of 512 echo-planar images (EPI) in resting human brain obtained every 250 ms reveals fluctuations in signal intensity in each pixel that have a physiologic origin. Regions of the sensorimotor cortex that were activated secondary to hand movement were identified using functional MRI methodology (FMRI). Time courses of low frequency (< 0.1 Hz) fluctuations in resting brain were observed to have a high degree of temporal correlation (P < 10(-3)) within these regions and also with time courses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

170
7,381
4
74

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 8,867 publications
(7,629 citation statements)
references
References 8 publications
170
7,381
4
74
Order By: Relevance
“…Similarly, participation of these regions for left-hand movements to the recovery of motor skills has amply been documented in stroke patients Rossini et al, 2003;Ward, 2005) or patients with a tumor or undergoing surgery (Duffau, 2000;Duffau and Capelle, 2001a,b;Krainik et al, 2004), or with multiple sclerosis (Rocca et al, 2005). More recently, studies of functional connectivity, particularly on healthy subjects in resting state (Biswal et al, 1995;Lowe et al, 1998;Xiong et al, 1999) have confirmed that these regions of the motor network are strongly correlated to one another.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, participation of these regions for left-hand movements to the recovery of motor skills has amply been documented in stroke patients Rossini et al, 2003;Ward, 2005) or patients with a tumor or undergoing surgery (Duffau, 2000;Duffau and Capelle, 2001a,b;Krainik et al, 2004), or with multiple sclerosis (Rocca et al, 2005). More recently, studies of functional connectivity, particularly on healthy subjects in resting state (Biswal et al, 1995;Lowe et al, 1998;Xiong et al, 1999) have confirmed that these regions of the motor network are strongly correlated to one another.…”
Section: Discussionmentioning
confidence: 94%
“…As a result, many methods are available to this end, including activation maps (Huettel et al, 2004), as well as methods deriving from functional connectivity, such as principal or independent component analysis (Friston et al, 1993b;Arfanakis et al, 2000), or correlation maps (Biswal et al, 1995(Biswal et al, , 1997Xiong et al, 1999). In our study, we assume that this step has been successfully completed, providing us with a set of regions and corresponding signals.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced neuroimaging techniques using magnetic resonance imaging (MRI) such as morphometry (Ashburner & Friston, 2000; Fischl & Dale, 2000) and resting‐state functional connectivity (rsFC) MRI (Biswal, Yetkin, Haughton, & Hyde, 1995) allow us to identify TBI with better sensitivity and precision. MRI‐based morphometry has revealed altered cortical thickness and volume within individuals who have sustained a TBI (Bendlin et al., 2008; Gale, Baxter, Roundy, & Johnson, 2005; Kim et al., 2008; Sidaros et al., 2009; Spitz et al., 2013; Tate et al., 2014; Turken et al., 2009; Warner et al., 2010; Zhou et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several specific approaches have been implemented (Horwitz, 2003), and their relative merits have not been established. The timeseries correlation method (Biswal et al, 1995;Lowe et al, 1998) examines interregional correlations within individual subjects over the timecourse of an experiment, and has been effectively applied to measure functional connectivity across a wide range of cognitive and physiological states (Li et al, 2000;Lowe et al, 2002;Greicius et al, 2003;Honey et al, 2003;Anand et al, 2005;Bartels and Zeki, 2005;Fox et al, 2005;Koshino et al, 2005;Menon and Levitin, 2005;Peltier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%